2012
DOI: 10.1089/end.2011.0214
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Retroperitoneal Lymph Node Dissection in an Adolescent Population

Abstract: Laparoscopic retroperitoneal lymph node dissection (RPLND) has been shown to be safe and effective in appropriately selected pediatric and adolescent patients with paratesticular rhabdomyosarcoma (RMS) and testicular germ-cell tumors (T-GCT). While the use of robot-assisted laparoscopy has expanded rapidly in many areas, there are very limited reports of its use with RPLND. We present two cases of adolescents who were treated using robot-assisted laparoscopic RPLND (R-RPLND)-one with paratesticular RMS (PT-RMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Our median operative time of 540 min was substantial compared with the adult literature (150–329 min) [24]; however, we performed bilateral re-sections in both cases. In addition, Cost et al reported a similar OT (527 min) for a post-chemotherapy, bilateral RPLND in a 15-year-old male [11]. In regards to ejaculatory function, one patient has regained antegrade ejaculation, whereas the other has not.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our median operative time of 540 min was substantial compared with the adult literature (150–329 min) [24]; however, we performed bilateral re-sections in both cases. In addition, Cost et al reported a similar OT (527 min) for a post-chemotherapy, bilateral RPLND in a 15-year-old male [11]. In regards to ejaculatory function, one patient has regained antegrade ejaculation, whereas the other has not.…”
Section: Discussionmentioning
confidence: 95%
“…In the current literature, there are only four case reports of robotic techniques for cancers with pathology similar to adults in adolescent patients, namely renal cell carcinoma [10] and two non-seminomatous germ cell tumors [11], and one report of robotic nephrectomy being used safely for Wilms’ tumor in an adolescent patient [12]. The reasons for this are multifactorial: 1) genitourinary (GU) malignancies in pediatric patients are rare, making it difficult to amass case volume, 2) when they do occur, many are too large or complex for minimally invasive techniques, 3) the current management strategies for pediatric GU cancers are largely successful, therefore the incentive to test new management approaches is limited, and 4) a majority of pediatric GU oncology cases are managed by general surgeons [8,9] who generally have lower rates of robotic utilization than urologists.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than focusing on the relatively straightforward pyeloplasties and ureteral reimplantations, complex reconstructive procedures have been described, including continent catheterizable channels,[4] robotic bladder augmentation with appendicovesicostomy robotic-assisted laparoscopic augmentation ileocystoplasty and Mitrofanoff appendicovesicostomy (RALIMA) or without (RALI),[5] bladder neck reconstruction,[6] and retroperitoneal lymph node dissection. [7] Large-scale series and long-term outcomes regarding these procedures have not yet been published, but early data are promising. At the very least, pediatric urologists have provided proof of principle that the most complex reconstructive surgeries can be performed robotically.…”
Section: Procedural Applications and Outcomesmentioning
confidence: 99%
“…In addition, robotic retroperitoneal lymphadenectomy for paratesticular rhabdomyosarcoma and testicular germ cell tumors have been performed with good functional and oncologic outcomes. [7]…”
Section: Procedural Applications and Outcomesmentioning
confidence: 99%
“…Moreover, robotassisted laparoscopic retroperitoneal lymph node dissection can be safely performed. 49 …”
Section: Futurementioning
confidence: 99%